Body size variation in a modern collection of mountain gazelle (Gazella gazella) skeletons. (February 2022) - Lebenzon, Roxanne; Munro, Natalie D.
Highlights: Sex is the most important determinant of gazelle body size. Humerus often used to sex gazelle, but males and females do not differ statistically. Hotter July temperatures shorten growing season and may relate to smaller bodies. Anthropogenic factors likely account for much unexplained variation in body size. Distal humerus recommended for the exploration of long-term body size change. Abstract: Two-dimensional measurements of skeletal elements are important zooarchaeological tools that not only provide crucial information about the sex and age of an animal, but on past environmental conditions and human-animal interactions as well. The causes of animal body size variation are many and thus problems of equifinality make it difficult to interpret archaeological measurement data. Here, we explore the sources of body size variation in a modern skeletal collection of mountain gazelle ( Gazella gazella ) composed of individuals of known sex, age and geographic location. We investigate the relative contribution of sex, age and environmental factors (temperature and precipitation) to variation in the 2D measurements of five commonly preserved skeletal elements (scapula, humerus, second phalanx, tibia and astragalus) to determine which factors are most influential. Overall, sex is the most powerful determinant of gazelle body size, while age has little impact on most elements. Importantly, although the breadth of the trochlea of the distal humerus has often been used to sex archaeological gazelle specimens, this element did not differ statistically for males and females. Maximum July temperature also influenced the distal depth of the tibia and the trochlea of the humerus. This may relate to reduced food availability during the critical period of juvenile growth in areas with hotter summers due to higher rates of evaporation and shorter growing seasons. The absence of a significant relationship between the other climatic variables and body size, and the large amount of variability that these factors could not account for, may relate to the confounding impact of anthropogenic activities. In recent decades human landscape modification and agriculture have impacted the natural scheduling of plant and water resources and gazelle population size.